2006
DOI: 10.4028/www.scientific.net/ssp.116-117.76
|View full text |Cite
|
Sign up to set email alerts
|

Hot Tearing Susceptibility and Fluidity of Semi-Solid Gravity Cast Al-Cu Alloy

Abstract: Aluminum-copper alloys offer both high strength and excellent ductility suitable for a number of automotive applications to reduce vehicle weight; however, the alloys are difficult to cast because of their tendency for hot tearing. In this work, semi-solid gravity casting of an aluminum-copper alloy, B206, was conducted in constrained rod casting molds to study the feasibility of using the process to reduce or eliminate hot tearing. To demonstrate the feasibility of gravity casting of the metal slurries, a flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 6 publications
1
12
0
1
Order By: Relevance
“…[18] It differs from the other alloys primarily in the lower titanium limit which is claimed to improves the alloy behaviour with respect to hot tearing by increasing its response to Ti-B based grain refiners for Ti-B additions in the range of 10-30 ppm boron. This claim was confirmed by Wannasin et al [16] who studied hot tearing susceptibility and fluidity of semi-solid gravity cast Al-Cu alloys at 5% fraction solid.…”
Section: History Applications and Properties Of 206 Alloyssupporting
confidence: 72%
See 1 more Smart Citation
“…[18] It differs from the other alloys primarily in the lower titanium limit which is claimed to improves the alloy behaviour with respect to hot tearing by increasing its response to Ti-B based grain refiners for Ti-B additions in the range of 10-30 ppm boron. This claim was confirmed by Wannasin et al [16] who studied hot tearing susceptibility and fluidity of semi-solid gravity cast Al-Cu alloys at 5% fraction solid.…”
Section: History Applications and Properties Of 206 Alloyssupporting
confidence: 72%
“…Each of the energy components can therefore be used to describe the ductility of the material with an advantage to the initiation energy, but total energy remains the perfect tool. Elongation (%) 16 …”
mentioning
confidence: 99%
“…In the present case, the fine globular microstructure obtained from the SEED process combined to the silicon addition provides a microstructure that reduced hot tearing sensibility. Moreover, the partially solidified metal results in less solidification contraction to compensate for strains by movement of both liquid and solid [4]. Consequently, the study of mechanical properties was based on variants of Alloy-II and Alloy-III using a silicon level around 1% and a copper level below 5%.…”
Section: Results and Discussion A) Hot Tearing Sensitivitymentioning
confidence: 99%
“…Semi-solid processing however offers new opportunities for these difficult to cast alloys due to the distinctive globular structure of the slurry and the lower amount of contraction that the castings undergo upon solidification. A previous study reported a reduction of hot tearing with semi-solid gravity casting with a solid fraction as low as 5% [4]. In that respect, a higher solid fraction is more likely to minimize hot tearing susceptibility in this alloy system.…”
Section: Introductionmentioning
confidence: 99%
“…Cette bonne performance des pièces semi-solides est possible grâce au fait que le métal partiellement solidifié procure des zones de contraction plus petites et rapprochées [44].…”
Section: Reduction Des Déchirures à Chaudunclassified